(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
James Neish reported that since his previous publication on the topic (see Vol III, pp.440-454), he had continued his excavations at the ruined walls on Laws Hill near Monifieth and hoped to produce an updated ground plan soon. Some of the artefacts that were found during his excavations were exhibited on the day. Meeting notes for 9 May, 1864 are appended. Also included are transcriptions of the letters read at this meeting from the Archaeological Institute of London to the Society about the restoration of Trinity College Church.